CLIL practice in a maritime English course: EFL students’ perception - Nurmala Elmin Simbolon (EduLite: Journal of English Education, Literature and Culture, 2020)
This article examines to what extent 'content and language integrated learning' or CLIL approach has impact on students’ learning in a Maritime English course. The graduates of Fishing Technology Study Program (TPI) in Advance University are required to have a certificate of nautical expert of fishing vessel (ANKAPIN) when applying for a job in a fishing vessel in Indonesia. One of the subjects assessed in the ANKAPIN examination is Maritime English. Bearing its name, this particular content subject consists of Maritime-related terminology and phrases. Believed as an effective way of learning a second, or a foreign language by integrating content and language learning, CLIL approach requires the collaboration between the lecturers of English and discipline subjects. The action research reported in this article implemented an English medium instruction (EMI) class using CLIL approach in an English as foreign language (EFL) context. The data collection included students’ pre-test and post-test results and questionnaires of student evaluation towards CLIL classroom learning. The results of the tests were analyzed descriptively using the Excel program and the evaluation survey was with content analysis. The results of this study showed students' increased understanding of vocabulary in the field of Maritime. Students also expressed their positive experience in the CLIL class. Besides, students articulated some more to experience including authentic learning aids such as a fishing vessel and more visual materials.